MANAJEMEN STRATEGIS PENGEMBANGAN MADRASAH ALIYAH MINHAJUL HAQ PURWAKARTA - Misna (UNISAN JURNAL, 2024)
The aim of this research is to analyze the managerial implementation of madrasa/school principals in institutional development in Madrasah Aliyah Minhajul Haq Purwakarta, to analyze the supporting factors for the managerial implementation of madrasa/school principals in institutional development in Madrasah Aliyah Minhajul Haq Purwakarta. To analyze the factors inhibiting the managerial implementation of madrasah/school heads in institutional development at Madrasah Aliyah Minhajul Haq Purwakarta. This type of research used a qualitative descriptive method. Data sources consist of primary data sources and secondary data sources. Data collection techniques in research are observation, interviews and documentation. Guaranteeing the validity of the data by using triangulation, which is a data validity checking technique that utilizes checking or comparison of the data. The research results show that the managerial implementation of madrasah/school heads in institutional development at Madrasah Aliyah Minhajul Haq Purwakarta is quite good and needs improvement in student management, curriculum management, infrastructure management and personnel management. The managerial implementation of madrasah/school heads in institutional development at Madrasah Aliyah Minhajul Haq Purwakarta is good in all five educational management areas.